Innovation in VET : Germany - Hensen-Reifgens, Kristina Alice [Verfasser]; Hippach-Schneider, Ute [Verfasser] (My University, 2015)
This article is the third one of a set of articles prepared within Cedefop's ReferNet network. It provides some examples of recent innovation initiatives in vocational education and training (VET) in Germany. (BIBB-Doku)
Keywords: Berufsbildung; Innovation; Innovationspreis